A method for tracking and evaluating students' physical activity using wearable devices - Kovalev A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to scientifically substantiate a system of pedagogical control of motor activity based on data from wearable devices. Methods and structure of the study. The work involved: theoretical analysis, generalization of data from scientific publications, statistical and rank analysis. Results and conclusions. The system, developed for monitoring and assessing the motor activity (MA) of those engaged in health-improving physical culture (HPE), is closely integrated with the process of setting physical activity standards. The key component is the information and analytical complex (IACOM), which includes a heart rate (HR) database, tools for analysis and visualization, and a user interface. Elements of the system of pedagogical control of motor activity (SPKDA) are built into each stage of standardization. The main activities for monitoring and assessing MA are shown in the figure. This system of pedagogical control expands the possibilities of personalized standardization of physical activity, providing the feedback necessary for effective management of the motor activity of those engaged in HPE.